Advanced crime scene photography - Duncan, Christopher D. (CRC Press, Taylor & Francis Group, 2015)
This new edition explains how to identify crime scene challenges, design plans to capture images correctly, and execute those plans successfully. The book also addresses a variety of topics including impression evidence, fire scenes, laser trajectories, macro-photography, and ultraviolet and infrared photography.